Seasonal, spatial and socioeconomic variations in the dietary pattern of two cities of Bangladesh: a food frequency questionnaire survey - Nazneen, Touhida; Chowdhury, Md Abul Khair; Hossen, Md Zakir; Rahman, M Hammadur; Quadir, Quazi Forhad (Asian-Australasian Journal of Bioscience and Biotechnology, 2016)
Two separate surveys were conducted in two cities of Bangladesh viz. Dhaka and Mymensingh to observe the seasonal as well as socio-economic variations in the dietary pattern. A total of 118 respondents were randomly selected and interviewed with a food frequency questionnaire (FFQ) to assess the dietary intake. Based on the respondents’ household income they were categorized into low income level (LIL); medium income level (MIL) and high income level (HIL) groups. Among the two cities, carbohydrate consumption was higher in Mymensingh during both winter (407 gp-1d-1) and summer (442 gp-1d-1). On the other hand, animal protein consumption was higher in Dhaka (176 gp-1d-1in summer and 283gp-1d-1 in winter). Usually in winter, carbohydrate consumption was lower but protein consumption was higher. There was no significant seasonal and spatial variation of plant protein consumption. However, leafy vegetable consumption was higher in Mymensingh during summer season (87 gp-1d-1). Overall, non-leafy vegetables consumption increases during winter and found highest in Dhaka (655 gp-1d-1). In general, water consumption was higher during summer and found highest in Mymensingh (3.8Lp-1d-1). Concerning the income groups, in both locations and seasons, carbohydrate consumption was observed lowest among HILs, but animal protein consumption was found highest, especially, in Dhaka. Rice is consumed in greater proportion than wheat among LILs and MILs. Wheat consumption was higher among HILs. Of all the animal proteins, fish and chicken were occupies the major portion. But dry fish consumption was relatively greater among LILs. In Dhaka, plant protein consumption was higher by MILs but in Mymensingh it was found highest among HILs. Both leafy and non-leafy vegetables consumption was higher by HILs in Mymensingh but among MILs in Dhaka. In general fat consumption was higher among HIL group in both locations. The Principal component analysis (PCA) revealed a strong interaction between the respondent characteristics and consumption of different food items. The respondent income and education was positively correlated with the consumption of animal and plant proteins, oils and spices but negatively correlated with carbohydrate and dry fish consumption. The present study investigated the socioeconomic and seasonal influence on dietary pattern in two locations of Bangladesh which can be an effective tool in estimating the dietary exposure of chemical contaminants. Asian Australas. J. Biosci. Biotechnol. 2016, 1 (3), 453-463